If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(2f + -4) = 0 Reorder the terms: 2(-4 + 2f) = 0 (-4 * 2 + 2f * 2) = 0 (-8 + 4f) = 0 Solving -8 + 4f = 0 Solving for variable 'f'. Move all terms containing f to the left, all other terms to the right. Add '8' to each side of the equation. -8 + 8 + 4f = 0 + 8 Combine like terms: -8 + 8 = 0 0 + 4f = 0 + 8 4f = 0 + 8 Combine like terms: 0 + 8 = 8 4f = 8 Divide each side by '4'. f = 2 Simplifying f = 2
| 3t+(-16)=35 | | 1.5*(x+1)-(0.5+2)= | | x+7.2=-8.6 | | 2(5c+5)= | | 2x-7+4x=-2+6+5x+2 | | .10x+.02(70)=.08(x+400) | | 2x+4+x=-1-7+3x | | 2*(0.5x+1.5)-3.5= | | -11n+18=-9n-2 | | (5+z)(5z+7)=0 | | x^2-3x+532=0 | | 9w-2w=14 | | .10x+.2(70)=.8(x+400) | | 5=2m+1 | | .35x+.46(400)=.45(x+400) | | -1=-0.33333333333333(1)+x | | 14y+y=180 | | 2x+2+130+3x+3=180 | | 64w-4=12 | | 120=6a+75b | | 2x+2+130=3x+3 | | 2x^2-2y^2-16x-28y+122=0 | | 32+7x-6=12x-4 | | 4x+11+25=10x | | 4x-4+100=13x-3 | | 6x+10+8x+1=109 | | -13=7-(-8) | | X-6=56-16(x+6) | | .45=(400*.46)+(x*.35) | | 5=-1.3333333(-1)+x | | C=5/9(58-32) | | y=-16t^2+96t+8 |